Evaluación de tres métodos de conservación (congelación, refrigeración, preservantes) de calostro de vacas holstein friesian a los 0, 15, 30, 45, 60 y 75 días en la parroquia de Machachi sector Chishinche - Llumigusin Quillupangui, Carlos David (2015)
Evaluation of three methods of preservation (freezing, refrigeration, preservatives) colostrum of Holstein Friesian cows at 0, 15, 30, 45, 60 and 75 days in the parish of Machachi Chishinche industry was held in Canton Mejía of the Pichincha Province located more than 2900 meters and in the laboratory, in order to determine the levels of immunoglobulins using the colostrometer, and immunoglobulin A with laboratory tests on 96 samples of colostrum. This study was conducted using the experimental methodology complete block design with lift, therefore the values of immunoglobulin was performed at present in colostrum in field research (colostrometer) and laboratory. Its importance lies mainly in seeing the presence of immunoglobulin A (IgA) in mg / ml of colostrum of Holstein Friesian through three types of preservation as are refrigeration, freezing and formaldehyde, up to 75 days with a sequence of 15 days to determine that type of conservation is effective when retain the immunoglobulin A....